a) ![\frac{dy}{dx}=-\frac{16x}{25y}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7B16x%7D%7B25y%7D)
b) ![\frac{dy}{dx}=-\frac{4x}{25\sqrt{1-\frac{x^2}{25}}}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7B4x%7D%7B25%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B25%7D%7D%7D)
c) The two expressions match
Answer:
a)
The equation in this problem is
![16x^2+25y^2=400](https://tex.z-dn.net/?f=16x%5E2%2B25y%5E2%3D400)
Here, we want to find
by implicit differentiation.
To do that, we apply the operator
on each term of the equation. We have:
![\frac{d}{dx}(16 x^2)=32x](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%2816%20x%5E2%29%3D32x)
(by applying composite function rule)
![\frac{d}{dx}(400)=0](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%28400%29%3D0)
Therefore, the equation becomes:
![32x+50y\frac{dy}{dx}=0](https://tex.z-dn.net/?f=32x%2B50y%5Cfrac%7Bdy%7D%7Bdx%7D%3D0)
And re-arranging for dy/dx, we get:
![50\frac{dy}{dx}=-32x\\\frac{dy}{dx}=-\frac{32x}{50y}=-\frac{16x}{25y}](https://tex.z-dn.net/?f=50%5Cfrac%7Bdy%7D%7Bdx%7D%3D-32x%5C%5C%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7B32x%7D%7B50y%7D%3D-%5Cfrac%7B16x%7D%7B25y%7D)
b)
Now we want to solve the equation explicitly for y and then differentiate to find dy/dx. The equation is:
![16x^2+25y^2=400](https://tex.z-dn.net/?f=16x%5E2%2B25y%5E2%3D400)
First, we isolate y, and we find:
![25y^2=400-16x^2\\y^2=16-\frac{16}{25}x^2](https://tex.z-dn.net/?f=25y%5E2%3D400-16x%5E2%5C%5Cy%5E2%3D16-%5Cfrac%7B16%7D%7B25%7Dx%5E2)
And taking the square root,
![y=\pm \sqrt{16-\frac{16}{25}x^2}=\pm 4\sqrt{1-\frac{x^2}{25}}](https://tex.z-dn.net/?f=y%3D%5Cpm%20%5Csqrt%7B16-%5Cfrac%7B16%7D%7B25%7Dx%5E2%7D%3D%5Cpm%204%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B25%7D%7D)
Here we are told to consider only the first and second quadrants, so those where y > 0; so we only take the positive root:
![y=4\sqrt{1-\frac{x^2}{25}}](https://tex.z-dn.net/?f=y%3D4%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B25%7D%7D)
Now we differentiate this function to find dy/dx; using the chain rule, we get:
(2)
c)
Now we want to check if the two solutions are consistent.
To do that, we substitute the expression that we found for y in part b:
![y=4\sqrt{1-\frac{x^2}{25}}](https://tex.z-dn.net/?f=y%3D4%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B25%7D%7D)
Into the solution found in part a:
![\frac{dy}{dx}=-\frac{16x}{25y}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7B16x%7D%7B25y%7D)
Doing so, we find:
(1)
We observe that expression (1) matches with expression (2) found in part b: therefore, we can conclude that the two solutions are coeherent with each other.